Whole genome sequence of the multi-resistant plant growth-promoting bacteria Streptomyces sp. Z38 with potential application in agroindustry and bio-nanotechnology - Dávila Costa, José Sebastián (2020)
The genus Streptomyces is widely recognized for its biotechnological potential. Due to a need to improve crops,clean up the environment and produce novel antimicrobial molecules exploiting Streptomyces has become apriority. To further explore the biotechnological potential of these organisms we analyzed the genome of thestrain Streptomyces sp. Z38 isolated from contaminated roots tissues. Our analysis not only confirmed the abilityof the strain to produce plant growth promoting traits but also a range of mechanisms to cope with the toxiceffect of heavy metals through genes involved in metal homeostasis and oxidative stress response. The production of silver nanoparticles indicated that Streptomyces sp. Z38 may find utility in Green, Grey and Redbiotechnology